The Effects Of Dietary Lipid Level And Source On The Growth And Body Composition Of The Malaysian Mahseer, Tor Tambroides - Andin, Victor Charlie Anak (2010)
The Malaysian mahseer, Tor tambroides is regarded as a highly valued fish in the country. Popular among sport fishing enthusiast and serve as a delicacy in many parts of this country, the Malaysian mahseer can fetch a very high price in the market, there is very limited studies on the nutrition, especially lipid studies, on the fish. The present study was conducted to determine the best lipid level inclusion in the fish’s diet and also a follow up study on the effect of different lipid source on the growth and body composition of the Malaysian mahseer.